2000
DOI: 10.1038/sj.leu.2401651
|View full text |Cite
|
Sign up to set email alerts
|

Molecular profile of Epstein–Barr virus infection in HHV-8-positive primary effusion lymphoma

Abstract: Primary effusion lymphoma (PEL) selectively involves the serous body cavities, occurs predominantly in immunodeficient patients and is infected consistently by human herpesvirus type-8. PEL is also frequently infected by EpsteinBarr virus (EBV). The precise pathogenetic role of EBV coinfection in PEL is not fully understood. The lymphoma fails to express the EBV transforming proteins EBNA-2 and LMP-1, whereas it expresses EBNA-1 (latency I phenotype). Some studies have hypothesized that other EBV-positive lymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 44 publications
1
45
0
Order By: Relevance
“…34,35 Mutational analysis of the BCL-6 gene was performed by DNA direct sequencing of a unique PCR product encompassing 739 nucleotides (positions +404 to +1142) of the BCL-6 5′ noncoding regions. 13,36 The choice of this fragment was based on the fact that Ͼ95% of BCL-6 mutations detected in B-DLCL fall within this region.…”
Section: Analysis Of Bcl-6 Mutations and Rearrangementsmentioning
confidence: 99%
“…34,35 Mutational analysis of the BCL-6 gene was performed by DNA direct sequencing of a unique PCR product encompassing 739 nucleotides (positions +404 to +1142) of the BCL-6 5′ noncoding regions. 13,36 The choice of this fragment was based on the fact that Ͼ95% of BCL-6 mutations detected in B-DLCL fall within this region.…”
Section: Analysis Of Bcl-6 Mutations and Rearrangementsmentioning
confidence: 99%
“…While PELs are almost universally KSHV positive, the majority of PELs have concomitant EBV infection (reviewed in Dourmishev et al, 2003;Drexler et al, 1998;Moore and Chang, 2001). EBV apparently establishes levels type II latency in PELs with low of LMP-1 expression (Callahan et al, 1999;Fassone et al, 2000;Horenstein et al, 1997;Lacoste et al, 2000).…”
Section: B Primary Effusion Lymphomamentioning
confidence: 99%
“…The hypothesis that certain strains of EBV are associated with malignant transformation or with certain tumor types has been an area of active investigation. EBV gene polymorphisms have been demonstrated in a variety of EBV-associated tumors, including endemic Burkitt's lymphoma, Hodgkin's disease, immune deficiency-related lymphomas, gastric carcinoma, and nasopharyngeal carcinoma, as well as in EBV-positive reactive tissues and cultured lymphoblastoid cell lines (Bhatia et al, 1996;Chang et al, 1999;Chen et al, 1998;Fassone et al, 2000;Greiner et al, 2000;Gutierrez et al, 1997;Habeshaw et al, 1999;MacKenzie et al, 1999;Sandvej et al, 2000;Wrightham et al, 1995). Although some earlier studies suggested association of particular EBV strains with certain malignancies (Bhatia et al, 1996;Gutierrez et al, 1997), many subsequent studies have not confirmed this and, instead, have concluded that EBV sequence differences reflect geographic variations rather than any oncogenic potential Chen et al, 1998;Fassone et al, 2000;Habeshaw et al, 1999;MacKenzie et al, 1999;Sandvej et al, 2000).…”
Section: E Pstein-barr Virus (Ebv) Is Found In Essentially Allmentioning
confidence: 99%
“…Laboratory Investigation • July 2002 • Volume 82 • Number 7 liferative disorder termed P-ala VI (Greiner et al, 2000) and a single case (1/11 studied) of primary effusion lymphoma termed P-alaЉ (Fassone et al, 2000). One of the Peruvian/Mexican-NL cases (NL4) of Gutierrez and coworkers was also similar, sharing the same five base substitutions but also had an additional mutation at codon 529 (Gutierrez et al, 1998).…”
Section: Ebna Polymorphisms In Us Nk/t-cell Lymphomamentioning
confidence: 99%